2013
DOI: 10.1051/0004-6361/201219517
|View full text |Cite
|
Sign up to set email alerts
|

Deep optical imaging of asymptotic giant branch circumstellar envelopes

Abstract: We report results of a program to image the extended circumstellar envelopes of asymptotic giant branch (AGB) stars in dust-scattered Galactic light. The goal is to characterize the shapes of the envelopes to probe the mass-loss geometry and the presence of hidden binary companions. The observations consist of deep optical imaging of 22 AGB stars with high mass loss rates: 16 with the ESO 3.6 m NTT telescope, and the remainder with other telescopes. The circumstellar envelopes are detected in 15 objects, with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
(43 reference statements)
1
19
0
Order By: Relevance
“…1a shows extended emission up to a projected radius of ∼ 1 at the two SCUBA-2 wavelengths and ∼ 4.5 at the PACS wavelengths. The SCUBA-2 extent seen is comparable to the optical extent seen by Mauron et al (2013). In addition, more than half of the emission is from the extended component at all wavelengths.…”
Section: Irc+10216supporting
confidence: 59%
“…1a shows extended emission up to a projected radius of ∼ 1 at the two SCUBA-2 wavelengths and ∼ 4.5 at the PACS wavelengths. The SCUBA-2 extent seen is comparable to the optical extent seen by Mauron et al (2013). In addition, more than half of the emission is from the extended component at all wavelengths.…”
Section: Irc+10216supporting
confidence: 59%
“…This is determined by photodissociation and hence the strength of the interstellar UV field. Mauron et al (2013) have shown, using dust-scattered light, that there is a steep gradient in the strength of the interstellar radiation field with Galactic radius, and the distribution of OB associations causes substantial local variations. In lower-metallicity and/or extragalactic environments, the interstellar UV field may be very different (e.g., McDonald et al 2015).…”
Section: Molecular Line Emissionmentioning
confidence: 99%
“…Our knowledge of the morphology of the dust CSEs has improved significantly due to observations in dust-scattered light (e.g., Mauron et al 2013;Sahai and Mack-Crane 2014), and through observations with the Herschel Space Observatory of thermal dust emission (e.g., Cox et al 2012a). In particular, the latter shows that on the larger scales there are significant departures from sphericity, but these are not necessarily connected to a non-isotropic mass loss.…”
Section: Circumstellar Morphologymentioning
confidence: 99%
“…To date, binary companions have been detected for only a small number of AGB stars with low mass-loss rates through composite spectra or light curves (Jorissen et al 2003). There are indications that a significant fraction of AGB stars have binary companions, such as elliptical CSEs (Mauron et al 2013) as expected from binary AGB stars (Huggins et al 2009), and spiral-shell patterns in the CSEs (Mauron & Huggins 2006;Mayer et al 2011Mayer et al , 2014Maercker et al 2012;Kim et al 2013;Cernicharo et al 2015;Decin et al 2015) modeled by AGB winds under the gravitational influence of binary companions (Theuns & Jorissen 1993;Soker 1994;Mastrodemos & Morris 1999;Kim & Taam 2012a, 2012b, 2012cKim et al 2013).…”
Section: Introductionmentioning
confidence: 99%